Efficacy of nikkomycin Z in murine CNS coccidioidomycosis: modelling sustained-release dosing. (16th July 2021) - Sass, Gabriele; Larwood, David J; Martinez, Marife; Shrestha, Pallabi; Stevens, David A
Abstract: Objectives: Meningitis is the most feared coccidioidomycosis complication. Nikkomycin Z (nikZ) is a chitin synthase inhibitor. A concern is short half-life, necessitating multiple dose/day regimens. We simulated extended release, providing nikZ in drinking water. Extended release would enhance convenience, and adherence, for patients. Methods: Coccidioides posadasii was injected intracerebrally into mice. Twelve day treatments began on Day 3. Fluconazole was given 100 mg/kg once daily (gavage); designed doses of nikZ 30, 100 or 300 mg/kg/day in drinking water. On Day 30 post-treatment, survivors were euthanized, brain cfu quantitated and cfu in other organs assessed. Results: nikZ was stable in drinking water. Survival was 11%, 50%, 70%, 90% and 100% in untreated controls, fluconazole and nikZ 30, 100 and 300 mg/kg/day, respectively ; nikZ 300 mg/kg/day was superior ( P  ≤   0.01) to fluconazole. Brains were sterilized in 0%, 20%, 86%, 89% and 80% of mice, respectively; nikZ 100 or 300 mg/kg/day was superior ( P  ≤   0.01) to fluconazole. Clearance of infection in other organs was similar. All decreased drinking after infection, causing nikZ mice to ingest less than the desired dose in early therapy; despite this, they recovered sufficiently to resume pre-infection drinking and designed drug intakes. Thus, when sickest, even less than the designed dose was sufficient to enable recovery. Conclusions: This efficacy supports the development of sustained-release nikZ. Decreased intake wouldn't be a factor in humans, receiving drug via extended-release pill or continuous IV infusion. In prior studies (twice daily nikZ) of murine coccidioidal meningitis, results were inferior, suggesting sustained release may provide both convenience and superior outcomes.